Erratum to 'On Percolation and the Bunkbed Conjecture'. (22nd July 2019) - Linusson, Svante
Abstract: There was an incorrect argument in the proof of the main theorem in 'On percolation and the bunkbed conjecture', in Combin. Probab. Comput. (2011) 20 103–117 doi: 10.1017/S0963548309990666 . I thus no longer claim to have a proof for the bunkbed conjecture for outerplanar graphs.